Reduction in size of the calcifying phytoplankton Calcidiscus leptoporus to environmental changes between the Holocene and modern Subantarctic Southern Ocean - Rigual-Hernández, Andrés S.; Langer, Gerald; Sierro, Francisco Javier; Bostock, Helen; Sánchez-Santos, José Manuel; Nodder, Scott Davidson; Trull, Tom W.; Ballegeer, Anne Marie; Moy, Andrew D.; Eriksen, Ruth; Makowka, Laura; Béjard, Thibauld M.; et al. (Frontiers in Marine Science, 2023)
The Subantarctic Zone of the Southern Ocean plays a disproportionally large role on the Earth system. Model projections predict rapid environmental change in the coming decades, including ocean acidification, warming, and changes in nutrient supply which pose a serious risk for marine ecosystems. Yet despite the importance of the Subantarctic Zone, annual and inter-annual time series are extremely rare, leading to important uncertainties about the current state of its ecosystems and hindering predictions of future response to climate change. Moreover, as the longest observational time series available are only a few decades long, it remains unknown whether marine pelagic ecosystems have already responded to ongoing environmental change during the industrial era. Here, we take advantage of multiple sampling efforts – monitoring of surface layer water properties together with sediment trap, seafloor sediment and sediment core sampling – to reconstruct the modern and pre-industrial state of the keystone calcifying phytoplankton Calcidiscus leptoporus, central to the global marine carbonate cycle. Morphometric measurements reveal that modern C. leptoporus coccoliths are 15% lighter and 25% smaller than those preserved in the underlying Holocene-aged sediments. The cumulative effect of multiple environmental factors appears responsible for the coccolith size variations since the Last Deglaciation, with warming and ocean acidification most likely playing a predominant role during the industrial era. Notably, extrapolation of our results suggests a future reduction in cell and coccolith size which will have a negative impact on the efficiency of the biological pump in the Southern Ocean through a reduction of carbonate ballasting. Lastly, our results tentatively suggest that C. leptoporus coccolith size could be used as a palaeo-proxy for growth rate. Future culture experiments will be needed to test this hypothesis.